2010
DOI: 10.1177/039139881003300205
|View full text |Cite
|
Sign up to set email alerts
|

HPLC Study of Uremic Fluids Related to Optical Dialysis Adequacy Monitoring

Abstract: The present study contributes new information on the removal of uremic retention solutes during hemodialysis and on the origin of the optical dialysis adequacy monitoring signal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…This has been confirmed also by earlier studies [11,12] . Moreover, HPLC studies have demonstrated that UA is an UV-absorbing solute in the studied wavelength range, and therefore influences the UV-signal substantially [13] . This explains why UA had the same wavelength maximum at both treatment modalities.…”
Section: Discussionmentioning
confidence: 95%
“…This has been confirmed also by earlier studies [11,12] . Moreover, HPLC studies have demonstrated that UA is an UV-absorbing solute in the studied wavelength range, and therefore influences the UV-signal substantially [13] . This explains why UA had the same wavelength maximum at both treatment modalities.…”
Section: Discussionmentioning
confidence: 95%
“…The typical UV monitoring curve of elimination of small water-soluble uremic toxins by dialysis has been presented, and details of liquid chromatographic analysis of spent dialysate discussed elsewhere by our group in connection with assessment of online dialysis dose monitoring by UV absorbance [10, 12, 13]. The peak of UA is well separated from peaks of PAR and its metabolites on the chromatograms [12] and any possibility of analytical interference of PAR+ metabolites in HPLC estimation of UA content in spent dialysate seems not to be possible.…”
Section: Discussionmentioning
confidence: 99%
“…The dialysate flow was 500 mL/min and the blood flow varied from 245 to 350 mL/min depending on the patient but was kept stable during dialysis session. Spent dialysate was sampled hourly or more frequently and the content of main well-known uremic toxins in samples were analyzed using high performance liquid chromatography as described previously [12, 13]. Chromatograms at the wavelengths of 254 and 280 nm were monitored and quantitative calculations were made on the basis of the peak areas on the chromatograms at 280 nm for uric acid (UA) and at 254 nm for PAR and its metabolites (PAR+M).…”
Section: Methodsmentioning
confidence: 99%
“…This difference could be explained by specific removal characteristics for creatinine compared to the net removal of the UV-absorbing chromophores contributing to the optically measured signal in spent dialysate. Despite that the online UV-absorbance at 280 nm was closest to the removal of small water-soluble non-protein bound solutes like urea, creatinine and uric acid [ 16,17 ], the overall removal pattern is far more complex because each uremic solute has still a distinctive distribution volume in the body and removal rate during dialysis. This is expressed also by independent components in the models, including several wavelengths, proposed in this study.…”
Section: Discussionmentioning
confidence: 99%